Pregunta
upstudy study bank question image url

\[ \frac{6}{x-4}=\frac{-3}{x+5}+\frac{27}{(x-4)(x+5)} \] Select the correct choice below and fill in any answer boxes in your choice. A. The solution set is \( \{\square \). (Simplify your answer.) B. There is no solution.

Ask by Barker Norton. in the United States
Jan 31,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solution set is \( \{1\} \).

Solución

To solve the equation: \[ \frac{6}{x-4} = \frac{-3}{x+5} + \frac{27}{(x-4)(x+5)} \] **Step 1: Determine the restrictions.** The denominators cannot be zero, so: \[ x - 4 \neq 0 \quad \Rightarrow \quad x \neq 4 \] \[ x + 5 \neq 0 \quad \Rightarrow \quad x \neq -5 \] **Step 2: Clear the denominators by multiplying both sides by \((x-4)(x+5)\).** \[ 6(x + 5) = -3(x - 4) + 27 \] **Step 3: Expand and simplify.** \[ 6x + 30 = -3x + 12 + 27 \] \[ 6x + 30 = -3x + 39 \] **Step 4: Solve for \(x\).** \[ 6x + 3x = 39 - 30 \] \[ 9x = 9 \] \[ x = 1 \] **Step 5: Verify the solution is within the allowed domain.** \(x = 1\) does not equal 4 or -5, so it's a valid solution. **Final Answer:** **A. The solution set is \( \{1\} \).**

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equation \[ \frac{6}{x-4}=\frac{-3}{x+5}+\frac{27}{(x-4)(x+5)}, \] first, we can combine the right side over a common denominator: \[ \frac{-3}{x+5}+\frac{27}{(x-4)(x+5)} = \frac{-3(x-4) + 27}{(x-4)(x+5)} = \frac{-3x + 12 + 27}{(x-4)(x+5)} = \frac{-3x + 39}{(x-4)(x+5)}. \] Now, we have \[ \frac{6}{x-4} = \frac{-3x + 39}{(x-4)(x+5)}. \] Next, multiply both sides by \((x-4)(x+5)\) to eliminate the denominators: \[ 6(x+5) = -3x + 39. \] Now, distribute on the left side: \[ 6x + 30 = -3x + 39. \] Adding \(3x\) to both sides gives: \[ 9x + 30 = 39. \] Subtracting \(30\) from both sides results in: \[ 9x = 9. \] Dividing by \(9\) yields: \[ x = 1. \] Lastly, we should check that \(x = 1\) doesn't make any original denominators zero. Since neither \(x-4\) nor \(x+5\) equals zero at \(x = 1\), we confirm the solution. A. The solution set is \( \{1\} \).

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad